Trade Policy and Macroeconomic Balance in the World Economy. (IMF Working Papers; Working Paper ;, 1988)
The paper explores the relationship between trade policy and current accounts. The effect on the current account of a change in protection at home and then abroad is analyzed, assuming that the exchange rate floats. The 'savings-and-investment approach' is used. It shows that there is no presumption that protection would reduce a deficit. With a fixed exchange rate, the effect on savings and investment is brought about by the reduction in absorption that is required to maintain internal balance when restrictions are imposed. A current account deficit or real appreciation may generate protectionist pressures stimulated by 'conservative resistance.'.